1996
DOI: 10.1088/0022-3727/29/3/025
|View full text |Cite
|
Sign up to set email alerts
|

Bursts of high-frequency plasma waves at an electric double layer

Abstract: The high-frequency (HF) oscillations, which are driven by the electron beam on the high-potential side of an electric double layer, are investigated in a laboratory experiment. A new HF probe design has made it possible to achieve a combination of absolute amplitude calibration and spatial resolution which, for such high frequencies, has not been achieved before. The HF waves convert about 20% of the beam energy to oscillations within a region extending from 100 to 400 Debye lengths on the high-potential side … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 23 publications
2
14
0
Order By: Relevance
“…19 Electron waves appear on the high potential side appear also in the simulations presented in this paper and in our recently published simulations of auroral flux tubes. 28 Such waves can scatter particles in velocity space, forming populations that are trapped between the double layer and the magnetic mirror.…”
Section: Conclusion and Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…19 Electron waves appear on the high potential side appear also in the simulations presented in this paper and in our recently published simulations of auroral flux tubes. 28 Such waves can scatter particles in velocity space, forming populations that are trapped between the double layer and the magnetic mirror.…”
Section: Conclusion and Discussionsupporting
confidence: 73%
“…Experiments, simulations, and theory showed that these spikes formed as electrons accelerated in a double layer entered a density gradient on its high potential side. [19][20][21][22] The modelling of auroral flux tubes has been approached in different ways. Knight 23 used a stationary kinetic model to find the current-voltage relationship of the flux tube, assuming a monotonic potential profile.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental device is named the Green Tank and is shown in Figure 1. It is described in detail elsewhere [ Gunell et al , 1996a]. It is operated in a cathode sheath configuration that was also used in several of the previous studies of the HF spike [ Gunell , 1997; Gunell et al , 1996b; Löfgren , 1999; Wendt , 2001].…”
Section: Apparatus and Diagnosticsmentioning
confidence: 99%
“…The beam travels through a narrow gap region, without significant electric fields. Such a gap region has been observed by satellites [3] and in laboratory experiments [14,18]. When a distinct gap region exists, there is a laminar flow of electrons through the double layer.…”
Section: The Downward Current Regionmentioning
confidence: 65%